1988
DOI: 10.1007/bf02431546
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of brain stimulation reward byΔ 9-tetrahydrocannabinol

Abstract: The present experiment explored whether delta 9-tetrahydrocannabinol (delta 9-THC), the psychoactive ingredient in marijuana, shares with other drugs of abuse the ability to facilitate brain stimulation reward acutely, as measured by electrical intracranial self-stimulation (ICSS). Laboratory rats were implanted with stimulation electrodes in the medial forebrain bundle, and trained to stable performance on a self-titrating threshold ICSS paradigm. delta 9-THC, at a dose believed pharmacologically relevant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
5
7

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(113 citation statements)
references
References 19 publications
3
98
5
7
Order By: Relevance
“…Evidence for acute reinforcing effects of THC comes from studies of brain stimulation reward, place preference and intravenous self-administration. Reward thresholds are decreased by THC administration in rats upon acute administration (Gardner et al 1988;Lepore et al 1996), and THC also produces a place preference (Lepore et al 1995). THC increases dopamine in the shell of the nucleus accumbens similar to that observed with other major drugs of abuse (Tanda et al 1997).…”
Section: Tetrahydrocannabinolsupporting
confidence: 53%
“…Evidence for acute reinforcing effects of THC comes from studies of brain stimulation reward, place preference and intravenous self-administration. Reward thresholds are decreased by THC administration in rats upon acute administration (Gardner et al 1988;Lepore et al 1996), and THC also produces a place preference (Lepore et al 1995). THC increases dopamine in the shell of the nucleus accumbens similar to that observed with other major drugs of abuse (Tanda et al 1997).…”
Section: Tetrahydrocannabinolsupporting
confidence: 53%
“…These models include intracranial electrical self-stimulation techniques. Consistent with a role of cannabinoids in the motivational effects of other events that can function as rewards or reinforcers, it has been shown that THC lowers the threshold for electrical brain-stimulation reward in Lewis and Sprague-Dawley rat strains, and that withdrawal from a single administration of THC can elevate brain-stimulation reward thresholds (Gardner et al, 1988;1989;Lepore et al, 1996;Gardner and Vorel, 1998). However, these findings contrast with the lack of THC effects in the Fisher rat strain (Lepore et al, 1996), and the lack of effects of the synthetic CB1 receptor agonist CP 55,940 using the same procedure and a comparable range of doses (Arnold et al, 2001).…”
Section: Subjective and Motivational Effects Of Cannabinoidsmentioning
confidence: 72%
“…It has been confirmed that Δ 9 -THC shares many features with classical drugs of abuse, such as cocaine and heroin (for review see Gardner and Vorel, 1998;Tanda and Goldberg, 2003;Lupica et al, 2004). For example, THC lowers electrical brain-stimulation reward thresholds (Gardner et al, 1988), and increases the firing rate of ventral tegmental area (VTA) dopaminergic neurons projecting to the nucleus accumbens (French et al, 1997;Gifford et al, 1997), resulting in increased extracellular levels of dopamine in the nucleus accumbens (e.g., Chen et al, 1990;Tanda et al, 1997). It has also been shown that chronic cannabinoid administration leads to other significant neurobiological changes that resemble those already described for other drugs abused by humans (Rodriguez de Fonseca et al, 1997;Diana et al, 1998;Tanda et al, 1999;see Tanda and Goldberg, 2003 for review).…”
Section: Subjective and Motivational Effects Of Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, THC is known to impact on aspects of reward processing by, for example, reducing reward thresholds for operant responding leading to brain-self-stimulation (Gardner et al, 1988;Gardner and Lowinson, 1991). Also, THC also has an indirect action on dopamine neurotransmission in the mesolimbic and mesocortical systems (Ameri, 1999;Gardner and Vorel, 1998;Tanda and Goldberg, 2003;Tanda et al, 1997), suggesting that the acute effects of THC include altered catecholamine activity within the corticolimbic pathways that mediate decision-making cognition (Scarna et al, 2005).…”
Section: Introductionmentioning
confidence: 99%